Joy as Contextualized Feeling: Two Contrasting Pictures of Joy in East Asian Yogācāra - Li, Jingjing (Journal of the American Academy of Religion, 2023)
In this article, I elaborate on the approach to joy preserved in East Asian Yogācāra texts authored by Xuanzang and his disciple, Kuiji. I argue that these Yogācāra Buddhists propose a contextualist approach that does not presume joy to be an emotion with an essential property but rather perceives joy as always contextualized in lifeworlds at the personal and interpersonal levels. As such, Xuanzang and Kuiji outline two contrasting pictures of joy to capture how it is experienced in the lifeworld of ignorance and the lifeworld of wisdom, respectively. Upon delineating what joy is and how it is experienced, I continue to explore what joy can promise. Since joy does not have an inherent property, people can always make a collaborative effort to recontextualize joy for inclusion and emancipation. As such, I hope to draw on the Yogācāra analysis of joy to enrich the feminist discussion on happiness.